Sosialisasi dan Edukasi Penerapan Coretax Administration System (CTAS) Sebagai Upaya Peningkatan Literasi Pajak UMKM di Desa Bira - Chris Dayanti Br. Ginting; Ahmad Nashiruddin Mushoddiq Rahman; Syafar Ahmad; Masdar Ryketeng; Nadhiyah Putri Wardana (LPPMK Universitas Ngurah Rai, 2025)
The Coretax Administration System (CTAS) is designed to facilitate the administration, reporting, and payment of taxes online. However, at the regional level, the utilization of this digital service has not been fully optimized due to the existing digital divide, which hinders the community from accessing and using modern taxation services. This community service activity aims to enhance public literacy, particularly among MSME actors, enabling them to understand digital tax administration processes, improve reporting compliance, and support the government’s efforts to establish a more efficient, transparent, and participatory taxation system. Based on the results of the post-test, the activity has been successfully implemented with positive outcomes, demonstrating an increase in tax literacy knowledge and skills in using the digital tax reporting system. Additionally, the initiative to establish a “tax-aware MSME community” in Bira Village has emerged as a concrete output, strengthening the sustainability of this community service program.